This is the sort of thing that drives me nuts with Maple.
in the example below, how do I factor (L-Lm) so that the answer is in the form L1 :=L(1-k) instead of -L(k-1)?
Lm := (simplify(k*sqrt(L*L)) assuming (0 < L));
Lm := k L
L1 := (factor(L - Lm) assuming (0 < L and 0 < Lm and 0 <= k));
L1 := -L (k - 1)
in this simple case, it is easy to understand the result. However, these kind of representations in more complex solutions may obfuscate the result making it difficult to interpret its meaning, where as the meaning may be more obvious if the simplification or factorization led to a result formatted more similarly to the way a human would do it. How do I get Maple to simplify things the more "traditional" way?